Association between Duration of Second Stage of Labour and Perinatal Outcomes among Mothers admitted in Labour at Mbarara Regional Referral Hospital, Uganda - Mayanja, Ronald; Chakurab, Andrew; Mubiru, Musa; Masembe, Sezalio; Nkonwae, Innoncent; Njagi, Joseph; Ssalongo, Wasswa; Ngonzi, Joseph (American Scientific Research Journal for Engineering, Technology, and Sciences (ASRJETS), 2016)
About four million babies die in the first 4 weeks of life annually. Most of the neonatal deaths occur in the first week mainly on the first day after delivery. The objective of our study was to determine the factors associated with poor perinatal outcomes among low risk mothers admitted in labour at Mbarara Regional Referral Hospital (MRRH). This was a retrospective cohort study of mothers on the postnatal ward of MRRH. The total number of respondents was 140. The duration of second stage was ≤30 minutes in 70.0% of the women. The number of women with poor feotal outcome was 27(19.3%). The poor outcomes included, birth asphyxia, fresh still birth and early neonatal death. The odds of having a good feotal delivery outcome was inversely proportional to time, with best results registered when delivery occurred within 30minutes OR, 4.9, 95% CI (1.8-13.1), weakening towards duration of ≥60 minutes with OR, 17.7, 95% CI (5.3-52.5). A second stage of labour lasting more than 60 minutes is associated with poor neonatal outcomes. For best perinatal outcomes we recommend if the second stage exceeds 60 minutes, labour should be re-assed and action should be taken to avoid further delay. To avoid poor neonatal outcomes, a second stage of labour lasting more than 60minutes requires continuous feotal monitoring.
Keywords: Perinatal; Risk; Early Labour